Raising Productivity and Reducing the Risk of Household Enterprises : Ghana Country Study - World Bank (Washington, DC, 2014)
Ghana has had a history of developing and sustaining the growth of the informal enterprises because of a broad recognition of their pivotal role in job creation and in poverty reduction. The Government of Ghana has established some of the most developed institutions for supporting informal sector activity, including the National Committee on the Informal Economy (NCIE) tasked with leading and coordinating the process of designing policies and interventions in support of the informal sector, and the National Board for Small Scale Industries (NBSSI) that promotes the development of micro, and small enterprises (MSEs), many of which are informal. Moreover, the Government has supported a large private apprenticeship program, and a national network of banks and microfinance institutions (MFIs) that cater to the needs of both the formal and informal sectors. It has facilitated the formation of national and local level associations, which advocate for informal enterprises with local and national governments. This policy note presents the main findings of the full two year study of household enterprises in Ghana. This study was undertaken by the World Bank on behalf of the NCIE. The lead consultant and author were Aba Quainoo of MEL consultants, Accra, Ghana. MEL consultants undertook all the field work for this study as well (discussed in sections two and three). The World Bank provided the analysis of the GLSS and other data for section one. The note is organized as follows: section one provides an overview of the importance of Household Enterprises (HEs) in the country's economy, and presents a profile of those who operate them; section two analyzes the main constraints to their growth and productivity; section three reviews existing policies, programs, and projects that are relevant to HEs and that affect their performance; and the last section concludes with policy recommendations with the end in view of raising the productivity and reducing the risks of HEs, thereby enhancing their role in economic development and poverty reduction in Ghana.